2007
DOI: 10.1002/jor.20459
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of proximal tibia anterior shear force during a vertical stop‐jump

Abstract: Anterior cruciate ligament (ACL) continues to be a significant medical issue for athletes participating in sports and recreational activities. Biomechanical analyses have determined that anterior shear force is the most direct loading mechanism of the ACL and a probable component of noncontact ACL injury. The purpose of this study was to examine the biomechanical predictors of proximal tibia anterior shear force during a stop-jump task. A biomechanical and electromyographic (EMG) analysis of the knee was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 55 publications
5
113
3
Order By: Relevance
“…The peak tibial anterior shear forces during sharp decelerating tasks range from 0.2 to 0.8 (3 BW). [37][38][39][40][41][42] Whereas the tasks and time points used for the analyses differ somewhat among these studies and our study, all of these tasks involve sudden deceleration motions, and the tibial anterior shear forces that we generally observed in SSL and URL are similar to those in the literature.…”
Section: Discussionmentioning
confidence: 47%
“…The peak tibial anterior shear forces during sharp decelerating tasks range from 0.2 to 0.8 (3 BW). [37][38][39][40][41][42] Whereas the tasks and time points used for the analyses differ somewhat among these studies and our study, all of these tasks involve sudden deceleration motions, and the tibial anterior shear forces that we generally observed in SSL and URL are similar to those in the literature.…”
Section: Discussionmentioning
confidence: 47%
“…The running-stop-jump task is an athletic maneuver frequently performed in various sports. [49][50][51] Participants had an approach run and then a 2-footed landing, with each foot landing on the corresponding force plate. The landing was followed by an immediate takeoff (vertical jump) for maximum height and landing back onto the force plates ( Figure 3).…”
Section: Immediate Posttestmentioning
confidence: 99%
“…The body disability in contraction generation and also disability in movement prediction can increase the ground reaction force dramatically [35]. Based on previous studies the increase of knee flexion angle leads to decrease in proximal anterior shear force [8,10]. Also, these studies showed that the maximum knee extensor moment corresponds to the knee anterior shear force [8].…”
Section: Discussionmentioning
confidence: 96%
“…The body acceleration increases and the lower limb muscles contract eccentrically during landing to support the body weight and acceleration. Therefore, these muscle forces can increase the anterior shear force by extensor mechanism [10]. Co-contraction of the lower limb muscles can absorb the forces applied on the knee, and as a result, it can reduce the forces applied on the knee ligaments [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation